The reflexive turn in key account management. Issue 11 (4th November 2014) - Vanharanta, Markus; J.P. Gilchrist, Alan; D. Pressey, Andrew; Lenney, Peter
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This study aims to address how and why do formal key account management (KAM) programmes hinder effective KAM management, and how can the problems of formalization in KAM be overcome. Recent empirical studies have reported an unexpected negative relationship between KAM formalization and performance. Design/methodology/approach – An 18-month (340 days) ethnographic investigation was undertaken in the UK-based subsidiary of a major US sports goods manufacturer. This ethnographic evidence was triangulated with 113 in-depth interviews. Findings – This study identifies how and why managerial reflexivity allows a more effectively combining of formal and post-bureaucratic KAM practices. While formal KAM programmes provide a means to initiate, implement and control KAM, they have an unintended consequence of increasing organizational bureaucracy, which may in the long-run hinder the KAM effectiveness. Heightened reflexivity, including "wayfinding", is identified as a means to overcome many of these challenges, allowing for reflexively combining formal with post-bureaucratic KAM practices. Research limitations/implications – The thesis of this paper starts a new line of reflexive KAM research, which draws theoretical influences from the post-bureaucratic turn in management studies. Practical implications – This study seeks to increase KAM implementation success rates and long-term effectiveness of KAM by conceptualizing the new possibilities offered by reflexive KAM. This study demonstrates how reflexive skills (conceptualized as "KAM wayfinding") can be deployed during KAM implementation and for its continual improvement. Further, the study identifies how KAM programmes can be used to train organizational learning regarding KAM. Furthermore, this study identifies how and why post-bureaucratic KAM can offer additional benefits after an organization has learned key KAM capabilities. Originality/value – A new line of enquiry is identified: the reflexive-turn in KAM. This theoretical position allows us to identify existing weakness in the extant KAM literature, and to show a practical means to improve the effectiveness of KAM. This concerns, in particular, the importance of managerial reflexivity and KAM wayfinding as a means to balance the strengths and weaknesses of formal and post-bureaucratic KAM.